A study on a multidimensional model of mum effect among IT students - Sakgasit Ramingwong (2018)
Mum Effect is an important software project risk. The risk indicates members of projects not speaking out when they are aware of problems; this silence in turn can lead to project failure. In a multi-cultural offshoring scenario, culture is very much likely to influence both the intensity and probability of mum effect. We have proposed a model for mum effect which identifies three causes, namely, communication gap, fear of consequences and team solidarity. This study demonstrates the relationships between cultural dimensions and potential causes of mum effect among IT students. Understanding the perceptions of students is important to better design courses on software project management in outsourced environments. © 2009 IEEE.